Theoretical overview of the innovation system for service sector: some remarks of research methodology - Minh, Dinh Tuan; Binh, Dinh Thi Thanh; Lien, Nguyen Thuy (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
Innovation in service sector as well as the innovation system for service sector has not been studied in Vietnam. The overall study on the innovation system of sertvice sector is necessary to indicate the specific features of this sector. On basis of these specific features of the innovation system of service sector the paper gives some remarks on research methodology to help better research works on innovation activities in service sector. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;"> Code: 20042401